OUTLINE FOR A THOUGHT OF DIFFERENCE AND OF BECOMING-DISABLED IN EDUCATION - Lopes, Rodrigo Barbosa [UNESP] (State Univ Rio De Janeiro, 2016)
We propose in this paper to draw the outline of a review and a clinic for the thinking of difference and of becoming-disabled in philosophical reflection on education. The chosen path goes through the analysis of concepts such as difference, becoming, ontology and event, relying specifically on Foucault's and of Deleuze's philosophies of difference, that notably deepened the diagnosis of philosophical currentness of these notions. We recognize, equally, that the study of modes of problematization is the methodological option that a philosophical work about deficiency should strive to promote an ontology of the becoming-disabled, which considers the disability no more, or just as the object of a scientific and pedagogical knowledge, but as problematization of differences and emission of singularities irreducible to the regime of Same, of Identical or of Similar. We summarily present three alternatives or possibilities to establish in education an ontology and politics of difference and of becoming-disabled: reversing the Platonism or conquer for the becoming an art of surfaces; proposing that the reorganization of the pedagogical work of the inclusive school sign up on the domain of practices; and thinking of the ontology of becoming-disabled under the sign of the event. We hope, finally, that this work contributes to deepen the study of philosophy of education on the analytic of disability, of production of differences and of practices of inclusion today.
Keywords: event; difference; becoming-disabled; ontology; problematization